The bacteriology of pleural infection by genetic and standard methods and its mortality significance. - Maskell, N; Batt, S; Hedley, E; Davies, C; Gillespie, S; Davies, R (2006)
BACKGROUND: Antibiotic choices for pleural infection are uncertain as its bacteriology is poorly described. METHODS: Pleural fluid from 434 pleural infections underwent standard culture and a screen for bacteria by amplification and sequencing of bacterial 16S ribosomal RNA gene. RESULTS: Approximately 50% of community-acquired infections were streptococcal, and 20% included anaerobic bacteria. Approximately 60% of hospital-acquired infections included bacteria frequently resistant to antibiotics (methicillin-resistant Staphylococcus aureus, 25%; Enterobacteriaceae, 18%; Pseudomonas spp., 5%, enterococci, 12%). Mortality was increased in hospital-acquired infection (hospital, 17/36 [47%]; community, 53/304 [17%]; relative risk, 4.24; 95% confidence interval, 2.07-8.69; p < 0.00001; chi(2), 1 df = 17.47) and in gram-negative (10/22 [45%]), S. aureus (15/34 [44%]), or mixed aerobic infections (13/28 [46%]), compared with streptococcal infection (23/137 [17%]) and infection including anaerobic bacteria (10/49 [20%]; p < 0.00001, chi(2), 4 df = 23.35). CONCLUSION: Pleural infection differs bacteriologically from pneumonia and requires different treatment. Antibiotics for community-acquired infection should treat aerobic and anaerobic bacteria. Hospital-acquired, gram-negative S. aureus and mixed aerobic infections have a high mortality rate.